In silico antimicrobial resistance profiling of 1,240 Stenotrophomonas maltophilia genomes: AMR gene prevalence, temporal evolution, and ST-specific associations - Laith B. Alhusseini; Firas Nabeeh Jaafar; Ahmed R. Alsharmani; Ebrahim Kouhsari; Mohammad Sholeh (PLoS ONE, 2026)
Stenotrophomonas maltophilia is an opportunistic pathogen with clinically important multidrug resistance, yet large-scale genome-based analyses integrating population structure, resistance determinants, and epidemiological metadata remain limited. We analyzed 2,419 publicly available genomes retrieved from NCBI GenBank. After quality control with CheckM, 2,389 assemblies passed filtering criteria, and species identity was further evaluated by average nucleotide identity using FastANI. A final curated dataset of 1,240 confirmed S. maltophilia genomes was retained for downstream analyses. Antimicrobial resistance determinants were identified using AMRFinderPlus, sequence types were assigned by multilocus sequence typing, and temporal, geographic, host-associated, and gene co-occurrence analyses were performed. The 1,240 genomes represented isolates collected between 1900 and 2025 from 40 countries. Geographic metadata were available for 1,239 isolates, host source for 1,239 isolates, and collection year for 1,105 isolates. Human-derived isolates predominated, whereas animal-derived isolates were rare and environmental isolates were absent. MLST assigned 876 isolates to 97 sequence types, with ST5, ST4, ST1, ST31, and ST162 as the most prevalent lineages. The resistome comprised 69 unique resistance-associated genes across 12 functional classes and showed a bimodal structure, with a highly conserved intrinsic core and a sparse accessory component. Core genes included emrA , emrB , emrC , smeF , blaL1 , aac (6′)- Iz , aph (6), aph (3′)- IIc , ermB , and ermC , most of which occurred at very high prevalence. In contrast, acquired determinants such as sul2 , tet (G), aadA2 , blaNDM-1 , blaGES-1 , and blaOXA-74 were infrequent. Plasmid replicons were also uncommon, supporting a predominantly chromosomal resistance architecture. Temporal analyses showed that intrinsic genes were present in the earliest available isolates, whereas acquired genes appeared only in recent decades and generally remained rare. Several acquired genes, including floR , aph (3′′)- Ib , aph (6)- Id , and aac (6′)- Ib4 , declined over time, while no acquired resistance determinant showed a significant increasing trend. Gene presence pattern and co-occurrence analyses identified dominant conserved resistome configurations and a smaller set of variable accessory modules associated with putative mobile genetic elements. Comparative analysis further showed enrichment of intrinsic efflux-associated determinants in clinical isolates, whereas non-clinical isolates carried a broader diversity of acquired aminoglycoside resistance genes. These findings indicate that the global resistome of S. maltophilia is dominated by conserved intrinsic, chromosomally encoded resistance determinants, whereas acquired resistance genes remain rare, sporadic, and lineage-associated. This curated genome-scale framework provides a resource for surveillance and for future studies linking resistome evolution, mobile genetic elements, and genotype-phenotype relationships.